Transporte e armazenagem de merenda escolar: uma análise do processo logístico para as escolas municipais da zona rural não indígena de Tabatinga – AM - Nascimento, Edwim Ricardo (Brasil, 2022)
The natural characteristics of the Amazon region require the use of a logistics that is efficient in meeting the cities and communities that exist in these places as far away and many are difficult to access. School meals should arrive in perfect physical condition and quality for consumption. The main objective of this research was to analyze the logistics process of school meals for non-indigenous rural communities in the municipality of Tabatinga overlooking the transport and storage of products activity. It used questionnaires in interviews with managers responsible for this logistical process for the analysis and formation of this article. It identified a complex work required for these steps logistics, so as to prevent external actions that may negatively influence the path.